Cultural Adaptation: A Study in Selected Poems of Victor Hernandez Cruz - Al-Sammarraie, Mohammed Nihad Nafea; Ismael, Nadia Ali (Al-Adab Journal, 2022)
This study aims at tracing the effect of the two worlds, Puerto Rico and the United States of America, on the poetry of the Latin American poet, Victor Hernandez Cruz (1949 - ). The study begins with a cultural background about the Puerto Rican indigenous culture and the Puerto Rican diaspora in the City of New York. The study, then, discusses one of Cruz’s poems focusing on the ideas of alienation, nostalgia, consciousness, and bilingualism tracing his cultural adaptation throughout the process. It is concluded with the fact whether Cruz culturally adapted to the U.S. literary mainstream or not.